Near-zero liquid discharge of desulfurization wastewater by electrodialysis-reverse osmosis hybrid system. (April 2021) - Zhang, Xinmiao; Zhang, Chenlin; Meng, Fanning; Wang, Chenghong; Ren, Pengfei; Zou, Qi; Luan, Jinyi
Abstract: Flue gas desulfurization system is widely used to remove the SOx in the refineries. However, this produces a large amount of desulfurization wastewater, which is difficult to treat under strict environmental laws. Therefore, the near-zero liquid discharge (near-ZLD) of desulfurization wastewater is an imperative requirement in the petrochemical industry. This study serves as one of the pioneering attempts to explore the near-ZLD of desulfurization wastewater via hybrid electrodialysis (ED)-reverse osmosis (RO) system. A lab-scale plant was established to evaluate the feasibility of the proposed system and optimize the operating parameters. Through this system, the wastewater was concentrated from about 78 g/L to over 230 g/L, while the conductivity of product water can reach 550 μS/cm or less. The concentrated stream was then frozen to reclaim high-purity sodium sulfate crystals. The product water can be directly discharged into water bodies or reused as industrial circulating water without any further treatment. This study proves the hybrid ED-RO system is an efficient near-ZLD approach for desulfurization wastewater treatment, which facilitates the production of freshwater and the reclaim of salt resources.